Relatedness and learner autonomy: a case study of an adult refugee learning English - Carson, Lorna (My University, 2007)
Ireland has only recently become a country of immigration and asylum. Provision of English language training is a priority both for refugees and for the host community. There has been very little research in Ireland on language provision for refugees. Wider studies of learning suggest that outcomes are enhanced by a classroom environment which fosters autonomous and self-determined behaviour. This paper presents the case of one individual from Moldova and examines his experience as a language learner particularly in terms of ?relatedness?. The case study analyses his profile as an adult who struggled with his roles as refugee and student, but who continued to apply himself to the task of learning English and demonstrated increased motivation and progress. Data was collected by multiple techniques, including participant observation, audio interviews with students and teachers, closed- and open-format attitudinal questionnaires, and archival data from school records. The findings of the study suggest that the patterns of goal-setting observed contribute to some increased intrinsic motivation, and the development of internalized extrinsic motivation congruent with learner needs.
PUBLISHED
Keywords: language learning; immigration